THE ROLE OF EDUCATIONAL PROFESSIONAL ETHICS IN BUILDING THE CHARACTER OF PROSPECTIVE INDONESIAN LANGUAGE TEACHER STUDENTS - fatayah, ayu nila; Stefani, Anggun; Anissa, Syeisa; Yustiani, Lulu (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
In this research, character education is really needed by prospective Indonesian language teacher students. The educational profession is a course that provides a platform for providing character education. This is intended to can know how a role of professional ethics for developing the character of prospective Indonesian language teacher students . Ethics is a profession that has guidelines and goals, an individual attitude that is noble, dignified and honorable. In this research we used a qualitative descriptive research method. This qualitative research aims to obtain answers in the form of opinions, responses, perceptions or descriptions. The results obtained and the discussion show that professional ethics have an important role in shaping the character of prospective Indonesian language teachers, especially in instilling moral values and character in students. Don't forget the role of educational professional learning which is a guide for students to improve the skills of Indonesian language teacher candidates in the process of implementing the learning that has been carried out so that the implementation can be carried out well in accordance with the ethics of the educational profession.